Diphthongs when Ibn Al-Jazari in his book published in the ten readings - Phonological study- (Journal of the College of Basic Education, 2022)
Assimilation in the language inserting the thing into the thing. It is said: I stuck the bridle in the mouth of the beast, i.e.: I inserted it into it ().And diphthong in the terminology: “He joins a consonant letter with another vowel letter without separating them with a movement or a stop, so that by intertwining them they become like one letter, the tongue rises from them at one height, and sticks to one place, and the letter becomes strong” ( )The Kufans and the Basrans differed in the word diphthong with mitigation and stress. For the Kufans, it is the housing of the signifier, i.e., the weight of verbs, and among the Basrans, the stress of the indicative is the weight of a verbal form of diphthong. From the second century AH, and Quranic studies witnessed the birth of this science in practical application in reading.It is not permissible.